Communication - Bialski, Paula; Brunton, Finn; Bunz, Mercedes (In Search of Media, 2019)
Contemporary communication puts us not only in conversation with one another but also with our machinery. Machine communication-to communicate not just via but also with machines-is therefore the focus of this volume. Diving into digital communications history, Finn Brunton brings to the fore the alienness of computational communication by looking at network timekeeping, automated trolling, and early attempts at communication with extraterrestrial life. Picking up this fascination with inhuman communication, Mercedes Bunz then performs a close reading of interaction design and interfaces to show how technology addresses humans (as very young children). Finally, Paula Bialski shares her findings from a field study of software development, analyzing the communicative forms that occur when code is written by separate people. Today, communication unfolds merely between two or more conscious entities but often includes an invisible third party. Inspired by this drastic shift, this volume uncovers new meanings of what it means "to communicate."